The indirect effect of nitrate on the soybean nodule growth and nitrogen fixation activity in relation to carbon supply - Hongwei Luan; Huidi Hu; Wei Li; Zhilei Liu; Xuesheng Liu; Xihai Zhang; Sha Li (BMC Plant Biology)
Abstract Background The mechanism of nitrate inhibiting soybean (Glycine max L. Merr.) nodulation and nitrogen fixation is still controversial. The aim of this study was to evaluate whether increased carbon allocation could mitigate the inhibitory effect of indirectly supplied nitrate on nodule nitrogen fixation Methods In this study, dual-root soybean plants were constructed with one side nodulated and the other side non-nodulated. Nitrate was applied to the non-nodulated lateral roots, either directly or following the girdling of the base of the non-nodulated root, to enhance carbon transport from the shoot o the nodulated side. After 2 days and 7 days of treatment, the nitrogen fixation capacity was assessed, nodule ultrastructure was examined, and the concentrations of sucrose, starch, and soluble sugars in roots and nodules on both sides were determined. Results Indirect nitrate supply significantly suppressed nodulation and nitrogen fixation, reduced sucrose and starch concentrations in nodules, and induced premature senescence of nodule structure. Enhancing carbon allocation to the nodules increase sucrose and starch levels, restored the integrity of the infected cell wall and peribacteroid membrane, and improved nitrogenase activity. Conclusions Increasing carbon distribution to nodules can restore the structural integrity of infected cells and alleviate the negative impact of indirect nitrate supply on soybean nitrogen fixation.